EUV Beam-Foil Spectra of Scandium, Vanadium, Chromium, Manganese, Cobalt, and Zinc - Elmar Träbert (Atoms, 2021)
Beam-foil extreme-ultraviolet spectra of Sc, V, Cr, Mn, Co and Zn are presented that provide survey data of a single element exclusively. Various details are discussed in the context of line intensity ratios, yrast transitions, delayed spectra and peculiar properties of the beam-foil light source.